Pancasila Democracy: Non-Systemic Legal Studies Charles Sampford - Triwahyuningsih (IHSA Institute, 2021)
The ethical orientation of the ideals of Pancasila democratic law as desired by the founding fathers is contained in the Preamble of the 1945 Constitution of the Republic of Indonesia paragraph IV, a structure of the Republic of Indonesia is formed which is sovereignty of the people based on the state philosophy, namely the values of